Equations of the Fibre Composite Plates - Świtka, R. (Engineering Transactions, 1992)
The paper is concerned with elastic fibre-composite plates. For the fibre composite the concept of two-phase medium presented in the works of Holnicki-Szulc was used. For the plate the hypothesis of Kirchhoff-Love is applied. The displacement equations of the plates loaded in-plane and transversely are developed, in which the coupling between the "disk state" and the "plate state" can be observed. The bending of the fibre composite plate is presented in more detail.